A philosophy of perception in Plato - Araújo, Hugo Filgueiras de (Revista Archai, 2025)
The aim of this paper is to defend that Plato ́s Philosophy, embodied in the Hypothesis of Forms, has in its scope an account of sense data and sensitivity. They do not have to be left out, as the secondary literature usually holds. In Theaetetus, Socrates analyses exhaustively the possibility of sensitivity be held as knowledge; In Phaedo, using the reminiscence argument, Plato admits that in order to have learning process and memory, it is necessary that we have two correlative and mutually necessary cognitive experiences, namely: a sensitive perception (aísthesis), which gives rise to anamneses, and the soul ́s contact to the Forms, which is prior to birth. This is so, because the individual can only have memory of what he knew beforehand. This paper holds therefore that there is a Philosophy of Perception in Plato.